2018
DOI: 10.1124/dmd.117.078360
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Pharmacokinetics and Pharmacodynamics Are Altered by P-Glycoprotein and Breast Cancer Resistance Protein Efflux Transporters in Mice

Abstract: To understand the systemic impact of breast cancer resistance protein (Bcrp) and P-glycoprotein (Pgp) deletion, untargeted metabolomics was performed on cerebral spinal fluid (CSF) and plasma of wild-type (WT) and Pgp and Bcrp double-knockout (dKO) rats anesthetized with ketamine-xylazine. We unexpectedly found elevated ketamine levels in both CSF and plasma of dKO versus WT rats. Therefore, the effect of these transporters was investigated on the 1) oral and intraperitoneal serum pharmacokinetics (PK) of keta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Three anesthetics were tested in the ranges that correspond to their respective plasma concentrations during anesthesia. Ketamine inhibited the frequency of SICs by more than 30% when used at 30 μM, which is around the plasma concentration of rats after intraperitoneal injection (Ganguly et al, 2018). Propofol and dexmedetomidine had no effect on the frequency of SICs, even at 40-fold of their clinically relevant concentrations (Franks, 2008; Plourde and Arseneau, 2017).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Three anesthetics were tested in the ranges that correspond to their respective plasma concentrations during anesthesia. Ketamine inhibited the frequency of SICs by more than 30% when used at 30 μM, which is around the plasma concentration of rats after intraperitoneal injection (Ganguly et al, 2018). Propofol and dexmedetomidine had no effect on the frequency of SICs, even at 40-fold of their clinically relevant concentrations (Franks, 2008; Plourde and Arseneau, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…In this experiment, the concentrations of the three general anesthetics were chosen based on their clinically effective ranges. For propofol, an agonist of GABA A receptors, the plasma concentration to induce loss of consciousness in rat is around 10 μM (Yang et al, 1995); For ketamine, an antagonist of NMDA receptors, the plasma concentration of rats after intraperitoneal injection is around 30 μM (Ganguly et al, 2018); For dexmedetomidine, an agonist of alpha2-adrenergic receptors, the plasma concentration causing unconsciousness is around 40 nM (Plourde and Arseneau, 2017). The experimental concentrations of three drugs were 0.1, 1, 10, 20, and 40-fold of their clinically relevant concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The high mortality rate occurred although spontaneous breathing per se without intubation or supplemental oxygen is unproblematic in rats under KX anaesthesia according to the literature; but in most cases describing KX anaesthesia, no statement is provided as to whether additional oxygen was administered [14–16, 2628]. Therefore, it must be assumed that oxygen is not commonly supplied during KX narcosis.…”
Section: Discussionmentioning
confidence: 99%
“…in mice following i.p. administration (Maxwell et al, 2006;Zanos et al, 2016;Ganguly et al, 2018), it is possible that the locomotor effects observed are due to ketamine action prior to metabolism, while the effects on negative affect are potentially attributed to ketamine metabolites including hydroxynorketamine (Li et al, 2015;Zanos et al, 2016). This hypothesis will need to be tested in future experiments.…”
Section: Discussionmentioning
confidence: 99%